Creating a knowledge supply chain for e-tourism curriculum design: Integrating knowledge management and supply chain management - Fu Jing (2018)
Higher education, as one of the most important knowledge providers and service suppliers to the society, is obliged to produce qualified intellectual products through the process of knowledge transfer and creation, which depends largely on the quality of knowledge and the way it is delivered within a curriculum. This research takes e-tourism, a relatively new discipline, as a case study, highlighting a knowledge supply chain is the potential solution to leverage the understanding of tourism industry needs and tourism curriculum provision. The paper begins with a competency gap analysis between knowledge demand and supply. It then applies the Supply Chain Operations Reference (SCOR) model to analyze the "as-is" situation of the present knowledge flow in curriculum design, and finally proposes a "to-be" conceptual framework by integrating tools and methods of knowledge management and supply chain management in a knowledge supply chain (KSC). This demonstrates that a KSC can help in achieving e-tourism requirements of higher education stakeholders at both industrial and academic levels Copyright © 2012, IGI Global.